Penerapan Metode Agile Pada Development Aplikasi Pengelolaan Data Magang Berbasis Web Menggunakan Framework Laravel - Ergy Rahmatan Ramadhan; Kamal Prihandani; Apriade Voutama (Peneliti.net, 2023)
The use of applications in managing apprentice data is crucial because it will affect the efficiency of management and archiving in apprenticeship activities. Based on the results of initial observations made through direct observation of the process of apprenticeship activities and data collection at the Faculty of Computer Science, Singaperbangsa University, Karawang, cases were found concerning the management of apprentice data which was still ineffective. Special attention is needed in handling this case which aims to facilitate administration, lecturers and students in apprenticeship activities. Each user only needs to access the application to manage internship activities, by introducing digital media to facilitate internship activities in the form of developing a web-based apprentice data management application by implementing the Laravel framework and agile methods. An application that can accommodate all the needs of internship activities with features that are not separate and can make it easier to archive apprentice data. Application development carried out in this research only takes 25 days or 3 weeks 4 days, by producing 5 (five) sprints.